MWCNT nanocomposite films prepared using different ratios of PVC/PCL: Combined FT-IR/DFT, thermal and shape memory properties - Koek, Mediha; Pekdemir, Mustafa Ersin; Oner, Ecem Oezen; Hekim, Seda (Elsevier, 2023)
Multi-wall carbon nanotube (MWCNT) mechanically strengthens the polymer and increases heat transfer within polymers as it increases its electrical properties. In this study, composites were produced by doping with poly e -caprolactone (PCL) / poly vinyl chloride (PVC) blend prepared at different ratios, with a fixed MWCNTs ratio of 0.1%. By doing this, it is aimed to examine the effect of polymers, which are blend components, for the MWCNT polymer blend composite. It has been observed that all of the composites have shape-memory effects. When the thermal properties of the MWCNT blend composite were examined, it was observed that the melting temperature increased with increasing PCL ratio, in addition, two-step mass loss occurred in all composites. From the opacity measurements, it was seen that the transparency increased as the PVC ratio increased. Additionally, it was determined that the peaks overlapped when the density functional theory (DFT) and experimentally derived Fourier Transform Infrared spectroscopy (FTIR) spectra were compared.
Keywords: Shape memory polymer; PCL; Nanocomposite; MWCNT; Opacity